Pharmacological study of edema induced by venom of the snake Bothrops asper (terciopelo) in mice - Chaves Mora, Fernando (1995)
The effect of several drugs on the edema-forming activity of Bothrops asper venom was studied plethysmographically using the mouse foot pad assay. Bothrops asper venom induced a dose-dependent edema which developed rapidly and peaked 1 hr after envenomation. Incubation of venom with EDTA before injection resulted in a significant reduction of edema. In addition, pretreatment with prazosin, indomethacin, dexamethasone, yohimbine and mepacrine resulted in a significant reduction in edema-forming activity. However, no inhibitory effect was observed when mice were pretreated with verapamil, nordihydroguaiaretic acid, pyrilamine, cimetidine and propranolol. When drugs were administered after venom injection, only prazosin and indomethacin were effective in reducing edema. These results suggest that B. asper venom-induced edema in the mouse foot pad model is mediated, at least partially, by metalloproteinases, phospholipase A2, eicosanoid products and activation of alpha 1 and alpha 2 adrenergic receptors.